Penerapan Metode Double Diamond Pada Aplikasi Mobile (Studi Kasus: Faznet Samarinda) - Rahmad Fitrianto; Hario Jati Setyadi; Muhammad Labib Jundillah (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2026)
Faznet Samarinda is a local internet service provider offering internet access to its customers. To enhance the user experience, a more attractive, intuitive, and functional mobile application design is required. This study aims to redesign the UI/UX of the Faznet application according to user needs using the Double Diamond method, which consists of the discover, define, develop, and deliver stages. Data were collected through literature studies, in-depth interviews, and observation of user comments on the Google Play Store. The outcome of this research is a new UI/UX design evaluated using usability testing with Maze and the System Usability Scale (SUS) questionnaire. Testing involving 20 respondents yielded a Maze score of 95 and an SUS score of 93, falling into the "Excellent" category with a "Grade A". These results indicate that the redesign successfully meets user needs and resolves previous issues.